A HYBRID RECONFIGURABLE COMPUTER-INTEGRATED MANUFACTURING CELL FOR THE PRODUCTION OF MASS CUSTOMISED PARTS - Hassan, N.; Bright, G. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT:Current manufacturing environments do not possess the flexibility required for massproducing custom parts. A solution